Sustainable supply chain design considering indicators of value creation. (July 2021) - Lucía Sabogal-De La Pava, Martha; Julio Vidal-Holguín, Carlos; Fernando Manotas-Duque, Diego; José Bravo-Bastidas, Juan
Highlights: Sustainable supply chain (SC) optimization model maximizing Market Value Added (MVA) Instead of using flow costs, Weighted Variable Costs are applied. The impacts of environmental and social issues on MVA and SC structure are analyzed. The formulation considers SC Balance Sheet and Income Statement financial reports. Abstract: The growing concern about environmental and social impacts resulting from industrial activities has rethought the problem of supply chain design, in which the environmental and social pillars must be considered in the design process. Although the optimization of economic performance has been the main objective on the design of supply chains, the integration of financial indicators into design models has not been widely developed. This article proposes a mathematical programming model for the design of a sustainable supply chain. The objective function of the proposed model is the maximization of the market value added as a measure of the accumulated economic performance. The formulation includes the application of weighted raw material, transportation, and production costs to correctly calculate the cost of goods sold, a feature widely ignored in the literature. Regarding the social dimension, the installation of plants and distribution centers in regions with low human development index is promoted, and in the environmental dimension, the equivalent tons of carbon dioxide emitted by the land transportation of goods are restricted. An optimization-based primal heuristic is used as a solution strategy for the resulting mixed integer non-linear programming model. Finally, the proposed model is applied to a case study, which demonstrates the importance of considering sustainability for supply chain configuration.